Cryptocurrency Volatility, Gharar, and Risk Perception in Islamic Economics: A Qualitative Descriptive Study - Tuasikal, Muhammad Abduh; Mubarak, Jaih; Ibdalsyah; Sanrego, Yulizar Djamaluddin (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The rapid growth of cryptocurrency investors in Indonesia has sparked debates about its legal status within Islamic jurisprudence. A key focus is the extreme price volatility of cryptocurrencies and whether this should be classified as gharar (excessive uncertainty) or simply as market risk. This study utilizes a normative-legal and doctrinal approach to differentiate between volatility, an inherent characteristic of modern financial instruments, and gharar, a prohibited element in Islamic contracts. The primary data for this research is sourced from classical fiqh texts and contemporary fatwas, while secondary data includes regulations and indexed academic studies on financial volatility. The findings indicate that although cryptocurrencies display higher volatility compared to stocks and gold, not all fluctuations can be classified as gharar fāḥish (excessive uncertainty). Instead, volatility should be viewed as market risk (al-ghurm), which is measurable, manageable, and tolerable under Islamic law, provided that transparency and risk-sharing mechanisms are in place. The study concludes that cryptocurrencies can be considered lawful property under Islamic law when they are free from ribā (usury), maysir (gambling), and excessive gharar, thereby providing a solid foundation for issuing fatwas and designing regulations.